Mycorrhizal associations of an invasive tree are enhanced by both genetic and environmental mechanisms. Issue 11 (28th February 2015) - Yang, Qiang; Wei, Shujuan; Shang, Lei; Carrillo, Juli; Gabler, Christopher A.; Nijjer, Somereet; Li, Bo; Siemann, Evan
Abstract : Biotic interactions involving exotic plants in their introduced ranges may differ from those of co‐occurring plant species and from interactions in their native ranges. When interactions are less negative, or more positive compared to native plant species, this may increase invasion success, and differences among ranges may cause changes in exotic plant traits. Here, we investigated arbuscular mycorrhizae (AM) associated with Triadica sebifera seedlings from populations in native (China) and introduced ranges (US) and with seedlings from US and China species within three co‐occurring genera ( Liquidambar, Ulmus, Celtis ) grown in multiple common gardens in both ranges. No general pattern of higher or lower AM colonization was found in the introduced range for China and US Celtis, Liquidambar, or Ulmus species. However, AM colonization was significantly higher for Triadica than for other genera, particularly in the introduced range, suggesting AM may improve Triadica 's invasion success. Triadica AM colonization was higher in US than China gardens, decreased with increasing soil nitrogen in China, but was independent of soil nitrogen in the US. This might reflect a different effect of soil fertility on this mutualism among ranges. Introduced Triadica populations had higher AM colonization than native populations, particularly in US gardens, implying a possible advantage from greater AM association in the introduced range. This is the first field study demonstrating post‐introduction changes in mycorrhizal colonization of an invasive species. It indicates that there are ecological and evolutionary components to the effect of positive interactions on plant invasions.